Plan de auditoría de gestión para el departamento de talento humano de las instituciones de educación superior - Acosta Robi, Laura Aurora (2019)
The current investigation consists in the Design of an Audit and Management Plan with the purpose of determine the level of efficiency and effectiveness of the process that moderate the internal control and measure the level of accomplishment of rules and quality standards. The first chapter highlights the importance of the topic and the contribution to the institution, and the content of the research……